Prime Graceful Labeling - Hameed Hassan, T.; Mohammad Abbas, R. (International Journal of Engineering and Technology, 2018)
A graph G with m vertices and n edges, is said to be prime graceful labeling, if there is an injection   from the vertices of G to {1, 2, ..., k} where k = min {2m, 2n} such that  gcd ( ( ),  ( )=1 and the induced injective function   from the edges of G to {1, 2, ..., k − 1} defined by  ( ) = |  ( ) − ( ) | , the resulting edge labels are distinct. In this paper path  , cycle Cn , star K1,n , friendship graph Fn , bistar Bn,n, C4 ∪ Pn , Km,2 and Km,2 ∪ Pn are shown to be Prime Graceful Labeling .